Tinjauan Sistematis Dampak Perubahan Iklim terhadap Kejadian Penyakit Demam Berdarah Dengue (DBD) di Asia Tenggara : Analisis Artikel Tahun 2016-2025 - Farah Fauziah Rahmasari; Fitri Kurniasari; Adang Bachtiar; Cicilya Candi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Dengue Hemorrhagic Fever (DHF) remains a significant public health issue in Southeast Asia, with its transmission closely linked to climatic factors such as temperature, rainfall, and humidity. Climate change has intensified these factors, leading to increased mosquito breeding, faster virus replication, and broader geographic spread. This systematic review aims to examine the impact of climate change on DHF incidence in Southeast Asia. Using Sytematic Review methods with PRISMA guidelines flow, articles published from 2016 to 2025 were identified from PubMed, Scopus, ScienceDirect, ProQuest, and SageJournal databases. Fourteen relevant studies meeting inclusion criteria were analyzed in this research.The findings indicate that temperatures, increased rainfall, and high humidity significantly contribute to higher DHF transmission by supporting mosquito survival and virus development. Seasonal outbreaks are often observed during rainy seasons, and extreme climate events such as El Niño and La Niña further influence case surges. Based on Systematic Review from various arcticles, climate change significantly affects Dengue Hemorrhagic Fever patterns in the Southeast Asia. Climatic factors such as temperature, rainfall, humidity, and extreme climate phenomena like El Niño and La Niña have been shown to accelerate the life cycle of Aedes aegypti mosquitoes, increase the virus transmission capacity, and expand the geographic distribution of dengue-endemic areas. Climate change, both seasonal and long-term, has the potential to exacerbate the burden of dengue fever in this region, particularly in tropical and subtropical areas that are vulnerable to climate impacts.